La Cour suprême et le rapatriement de la constitution : la victoire du compromis sur la rigueur - Duplé, Nicole (Les Cahiers de droit, 1981)
On September the 28th 1981, the Supreme Court of Canada made public its opinion as to the constitutionaly of the Federal government's plan to repatriate and amend the B.N.A. Act. Modifications affecting provincial powers require, according to convention, the existance of which is recognized by six of the Judges, a certain degree of provincial consensus. The federal projet, contested by eight of the ten provinces, was therefore considered unconstitutional by a majority of the Judges. The Court mentioned furthermore that the federal plan, should it become law, would impinge upon the distribution of powers set forth in the B.N.A. Act. Seven of the nine Judges so deciding declared, on the other hand, that the Senat and House of Commons' resolution pertaining to the plan of repatriation and amendement was perfectly legal and that the British Parliament was, in law, the only authorized body to bring about the changes sought by said plan.